Analisis Turbin Hidrokinetik Savonius Biomimetik Berbasis Kontur Tubuh Ikan Haruan (Channa striata) pada Kecepatan Aliran Rendah - Rendi; Ahmandi Amin (Politeknik Negeri Semarang, 2026)
This study aims to investigate the effect of a biomimetic blade design based on the body contour of the snakehead fish (Channa striata) on the torque characteristics of a Savonius hydrokinetic turbine. The biomimetic concept was applied to the turbine blade geometry to evaluate its potential for improving hydrodynamic performance compared with a conventional Savonius turbine. The research was conducted using Computational Fluid Dynamics (CFD) simulations by comparing the moment coefficient (Cm) distribution as a function of rotor angular position for both biomimetic and conventional turbine configurations. The analysis was performed over a complete rotor revolution to identify torque generation characteristics and the influence of blade geometry on turbine performance. The results show that both turbine configurations exhibit similar moment coefficient distribution patterns, with the maximum moment coefficient occurring at rotor angles of approximately 30°–40° and the minimum moment coefficient occurring at rotor angles of approximately 110°–130°. However, the conventional Savonius turbine demonstrated superior performance compared with the biomimetic design. The maximum moment coefficient of the conventional turbine reached approximately 0.35, whereas the biomimetic turbine achieved only about 0.20. In addition, the biomimetic turbine produced a more negative minimum moment coefficient of approximately −0.40 compared with −0.30 for the conventional turbine. These findings indicate that the snakehead fish-inspired blade geometry employed in this study has not yet enhanced the rotor's torque-producing capability nor effectively reduced the adverse effect of the returning blade. Nevertheless, the proposed biomimetic concept remains promising and warrants further investigation through optimization of blade profile, blade orientation, overlap ratio, aspect ratio, and operating conditions to achieve improved hydrokinetic turbine performance